2022
DOI: 10.1007/s10565-021-09680-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylome and transcriptome changes induced by inorganic nanoparticles in human kidney cells after chronic exposure

Abstract: The unique physicochemical properties make inorganic nanoparticles (INPs) an exciting tool in diagnosis and disease management. However, as INPs are relatively difficult to fully degrade and excrete, their unintended accumulation in the tissue might result in adverse health effects. Herein, we provide a methylome–transcriptome framework for chronic effects of INPs, commonly used in biomedical applications, in human kidney TH-1 cells. Renal clearance is one of the most important routes of nanoparticle excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…80 We have shown that chronic exposure to inorganic NPs in human kidney cells caused genome-wide DNA methylome and transcriptome changes. 27 Additionally, significant changes in global DNA methylation were determined in white blood cells from nanomaterial-handling workers 81 and those occupationally exposed to nanocomposite material. 82 Epigenetic alterations might be valuable indicators of adverse health effects of NPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 We have shown that chronic exposure to inorganic NPs in human kidney cells caused genome-wide DNA methylome and transcriptome changes. 27 Additionally, significant changes in global DNA methylation were determined in white blood cells from nanomaterial-handling workers 81 and those occupationally exposed to nanocomposite material. 82 Epigenetic alterations might be valuable indicators of adverse health effects of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…26 The vast majority of published data come from in vitro studies, mainly after short-term (24-72 h) exposure. 20,27 Integrating conventional toxicological approaches with omics analyses contribute to our comprehension of the MNPstriggered adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Soltysova et al also identified FOS was downregulated in kidney cells after chronic exposure to inorganic nanoparticles. 67 …”
Section: Discussionmentioning
confidence: 99%